Creating dialogues in the Islamic Studies classsrooms: a comparative study of traditional pedagogy vs. critical pedagody - Hussien, Suhailah; Edwar, Lissa (2012)
The aim of the study is to examine whether Islamic Studies teachers at two private national high schools in Jakarta, Indonesia encourage critical thinking using dialogue practice of critical pedagogy. The two teachers are observed and interviewed, while a group of five students from each teacher’s class are also interviewed in a group. The findings revealed that Teacher A adopted a dialogue practice as expounded by critical pedagogy, while Teacher B created dialogues of traditional pedagogy. Students taught by Teacher A found the Islamic Studies class to be interesting and they are also participating actively in the classrooms. They are also able to critically discuss about issues, which have the potential to make them more conscious of their faith and also practices as Muslims. However, students taught by Teacher B are less interested in Islamic Studies and could not find it to be relevant to their daily lives. Hence, creating dialogue practice of critical pedagogy could result in the development of Muslims who think critically and practise Islam as a way of life.